Impact of Dripline Spacing on Cotton Growth and Yield - Siag, M; Kaushal, M P; Buttar, G S (Journal of Agricultural Engineering, 2010)
An experiment was conducted at PAU Regional Station, Bathinda, to study the impact of different spacing of surface drip lines and irrigation levels (0.6, 0.8 and 1.0 PET) on cotton growth and yield. The results revealed that cotton yield and water use efficiency (WUE) under drip was significantly higher than conventional flood irrigation. Maximum yield was achieved under drip line for each row of crop with irrigation level of 0.8 PET, whereas WUE was recorded for the same drip line spacing, but at 0.6 PET irrigation level. The initial growth (as reflected by leaf area index) was retarded for drip line in between two rows of crop as compared to drip line for each row of crop, but the rate of growth were similar for all drip line spacing after 45 days of sowing.